Answer:
3 sides
Step-by-step explanation:
Two sides will have the same angle measurement while the third angle will be different.
we have
![(9x^{2}+8x)-(2x^{2}+3x)](https://tex.z-dn.net/?f=%289x%5E%7B2%7D%2B8x%29-%282x%5E%7B2%7D%2B3x%29)
Step 1
Eliminate the parenthesis
![(9x^{2}+8x)-(2x^{2}+3x)=9x^{2}+8x-2x^{2}-3x](https://tex.z-dn.net/?f=%289x%5E%7B2%7D%2B8x%29-%282x%5E%7B2%7D%2B3x%29%3D9x%5E%7B2%7D%2B8x-2x%5E%7B2%7D-3x)
Step 2
Group terms that contain the same variable
![9x^{2}-2x^{2}+8x-3x](https://tex.z-dn.net/?f=9x%5E%7B2%7D-2x%5E%7B2%7D%2B8x-3x)
Step 3
Combine like terms
![7x^{2}+5x](https://tex.z-dn.net/?f=7x%5E%7B2%7D%2B5x)
therefore
the answer is
![7x^{2}+5x](https://tex.z-dn.net/?f=7x%5E%7B2%7D%2B5x)
Answer:
answer may verydo it your self
=7,892 , you could write out your numbers, then line them up to then add them.
Answer:
1) We have to multiply both sides by 1/(de)
2) c=ab/(cd)
Step-by-step explanation:
We have to achieve the right side expression be c only. To do that we have to multiply cde by 1/(de) . However we have to multiply the left side by
1/(de) as well.
So the resulting left side expression is:
ab *1/(de)=ab/(de)
So c= ab/(de)